A piezoelectric fiber composite material with an alternating multilayer structure and a preparation method thereof
Through the design of piezoelectric fiber composite materials with alternating multi-layer structures, combined with electrospinning and hot pressing treatment technology, the shortcomings in energy density and sensitivity of existing piezoelectric materials are solved, and the coexistence of high breakdown strength and high polarization level is achieved.
Patent Information
- Application Number
- CN202310103092.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-01-29
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2043-01-29
AI Technical Summary
While improving energy density and sensitivity, existing piezoelectric materials are difficult to achieve high polarization and high breakdown strength at the same time, and dielectric and energy storage performance are insufficient.
Using piezoelectric fiber composite materials with alternating multi-layer structures, piezoelectric fiber layers and dielectric elastomer fiber layers doped with conductive fillers are prepared through electrospinning technology. Combined with hot pressing treatment technology, the advantages of the two dielectrics can be combined.
It achieves the technical effect of coexisting high breakdown strength and high polarization level, improves the sensitivity and energy storage density of piezoelectric fiber materials, and also has excellent mechanical properties.
Smart Images

Figure CN115976742B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of piezoelectric nanofiber modified materials, and in particular to a piezoelectric fiber composite material with an alternating multilayer structure and a preparation method thereof. Background Art
[0002] With the development of wearable electronic products and the challenge of energy crisis, more efficient and sustainable energy devices have high practical application value. Piezoelectric materials can realize the energy conversion of mechanical energy and electrical energy based on the piezoelectric effect. The biomechanical energy of the human body such as finger tapping and knee bending is an ideal power source for wearable energy devices. Piezoelectric nanogenerators provide a new way to convert the biomechanical energy of the human body into electrical energy.
[0003] As typical piezoelectric polymers, polyvinylidene fluoride (PVDF) and its copolymers have good chemical stability, good flexibility and biocompatibility; it mainly has three different crystal forms, namely α, β, and γ phases, among which the β phase has the best piezoelectric response and the largest unit dipole moment. The piezoelectricity of PVDF and its copolymers is mainly related to the content of the β phase. Generally speaking, the more the β phase content, the stronger the piezoelectricity.
[0004] Traditional piezoelectric sensors with metal electrodes have some defects: strong rigidity, difficulty in miniaturization, easy disconnection between functional materials and electrodes, poor durability, etc. Compared with traditional piezoelectric materials, PVDF-HFP nanofiber membranes prepared by electrospinning technology have good flexibility, light weight, wide response frequency, hydrophobic and breathable, safe and environmentally friendly, etc. It is a good flexible piezoelectric material, but pure PVDF-HFP membranes cannot meet special application requirements, such as high energy density, high energy conversion efficiency and high sensitivity. As we all know, the energy density U e It symbolizes the energy storage capacity of the material. As can be seen from the following formula, U e Usually determined by the dielectric constant and breakdown strength of the material:
[0005]
[0006] In the above formula, ε r is the relative dielectric constant of the material, and ε0 is the dielectric constant of vacuum.
[0007] The method of introducing conductive fillers to increase the dielectric constant of polymers will inevitably lead to an increase in the dielectric loss of the material and a decrease in the breakdown strength, thereby reducing the energy storage density, which is not what we want to achieve.
[0008] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention and should not be regarded as an acknowledgment or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art. Summary of the invention
[0009] Purpose of the Invention
[0010] In order to solve the above technical problems, the purpose of the present invention is to provide a piezoelectric fiber composite material with an alternating multilayer structure and a preparation method thereof, which has high polarization, high breakdown strength, excellent dielectric properties, piezoelectric properties, energy storage properties, and low elastic modulus.
[0011] Solution
[0012] In order to achieve the above-mentioned purpose of the present invention, the present invention provides the following technical solutions.
[0013] In a first aspect, the present invention provides a piezoelectric fiber composite material, which is a multi-layer composite structure, formed by alternately stacking piezoelectric fiber layers and dielectric elastomer fiber layers and undergoing a heat pressing process.
[0014] In a specific embodiment, the structure of the piezoelectric fiber composite material is as follows from bottom to top:
[0015] (piezoelectric fiber layer-dielectric elastomer fiber layer) n;
[0016] Wherein, n is an integer between 1-10, preferably an integer between 1-5.
[0017] In a preferred embodiment, the piezoelectric fiber layer is made of a piezoelectric polymer doped with a conductive filler by an electrospinning process;
[0018] Optionally, the piezoelectric polymer is selected from: P(VDF-HFP), PVDF, PVDF-TrFE, PAN, preferably P(VDF-HFP);
[0019] Optionally, the conductive filler is selected from: MXene, CNT, GO, ILs, preferably MXene;
[0020] As a new type of two-dimensional transition metal carbide, MXene has good conductivity and excellent mechanical properties. The surface of MXene is rich in hydroxyl (-OH) groups. Due to the van der Waals force, the -OH groups on the surface of MXene can be electrostatically attracted to the F or H atoms on the surface of piezoelectric polymers P (VDF-HFP), PVDF, and PVDF-TrFE, thereby forming hydrogen bonds. At the same time, more dipoles are formed under the action of an external electric field, which is conducive to the transformation of piezoelectric polymers such as P (VDF-HFP) from the α phase to the β phase, thereby improving the piezoelectric properties of these piezoelectric fibers.
[0021] Preferably, in the piezoelectric fiber layer, the doping amount of the conductive filler accounts for 0.5%-3% (w / w) of the piezoelectric polymer;
[0022] Preferably, the parameters of the electrospinning process are as follows:
[0023] The spinning distance is 14-16cm; the positive high voltage is 14-17kV, and the negative high voltage is 2kV; the spinning injection speed is 0.2mm / min-0.4mm / min; and the spinning environment humidity is 50%-60%.
[0024] In a preferred embodiment, the dielectric elastomer fiber layer is made of a dielectric elastomer polymer by an electrospinning process;
[0025] Wherein, the dielectric elastomer polymer is selected from: polyurethane, polyacrylate;
[0026] Preferably, the electrospinning process parameters are as follows:
[0027] The spinning distance is 14-16cm; the positive high voltage is 16-24kV, and the negative high voltage is 2kV; the spinning injection speed is 0.2mm / min-0.4mm / min; and the spinning environment humidity is 50%-60%.
[0028] Preferably, the temperature of the hot pressing treatment is 25-40°C, the time of the hot pressing treatment is 1-10 min, and the pressure of the hot pressing treatment is 0.3-1 MPa.
[0029] In a second aspect, the present invention provides a method for preparing the piezoelectric fiber composite material as described in the first aspect, the preparation method comprising the following steps:
[0030] 1) adding a conductive filler into a solvent I, stirring with ultrasound until uniform dispersion, then adding a piezoelectric polymer thereto, heating and stirring, to obtain a piezoelectric polymer solution doped with a conductive filler;
[0031] 2) electrospinning the piezoelectric polymer solution obtained in step 1) to obtain a first piezoelectric fiber layer;
[0032] 3) dissolving the dielectric elastomer polymer in solvent II, heating and stirring to obtain a dielectric elastomer polymer solution;
[0033] 4) electrospinning the dielectric elastomer polymer solution obtained in step 3) on the first piezoelectric fiber layer obtained in step 2) to obtain a first dielectric elastomer fiber layer;
[0034] 5) According to the methods of steps 2) and 4), the piezoelectric fiber layer and the dielectric elastomer fiber layer are spun layer by layer from bottom to top in an alternating order to prepare a piezoelectric fiber composite structure layer;
[0035] 6) The piezoelectric fiber composite structure layer obtained in step 5) is subjected to heat pressing treatment to tightly combine adjacent piezoelectric fiber layers and dielectric elastomer fiber layers to obtain the piezoelectric fiber composite material.
[0036] Preferably, in step 1), the conductive filler is selected from: MXene, CNT, GO or IL, preferably MXene;
[0037] Optionally, the piezoelectric polymer is selected from: P(VDF-HFP), PVDF, PVDF-TrFE or PAN, preferably P(VDF-HFP);
[0038] Optionally, the solvent I is N,N-dimethylformamide and / or acetone, preferably a mixed solvent of N,N-dimethylformamide and acetone, further preferably a mixed solvent of N,N-dimethylformamide and acetone in a volume ratio of (3-2):(2-3), and most preferably a mixed solvent of N,N-dimethylformamide and acetone in a volume ratio of 3:2;
[0039] Optionally, the amount of the conductive filler is 0.5%-3% (w / w) of the amount of the piezoelectric polymer;
[0040] Optionally, the mass volume percentage (in g / ml) of the piezoelectric polymer in the solvent I is 20% to 25% (w / v), preferably 20% (w / v);
[0041] Optionally, the ultrasound frequency is 40 kHz, the power is 60-100 W, and the ultrasound time is 0.5-4 h.
[0042] Preferably, in step 2), the electrospinning parameters are as follows:
[0043] The spinning distance is 14-16cm; the positive high voltage is 14-17kV, and the negative high voltage is 2kV; the spinning injection speed is 0.2mm / min-0.4mm / min; the spinning environment humidity is 50%-60%;
[0044] Further preferably, the parameters of the electrospinning are as follows:
[0045] The spinning distance is 16 cm; the positive high voltage is 16 kV, and the negative high voltage is 2 kV; the spinning injection speed is 0.25 mm / min; and the spinning environment humidity is 55%-60%.
[0046] Preferably, in step 3), the dielectric elastomer polymer is selected from: polyurethane, polyacrylate;
[0047] Optionally, the solvent II is N,N-dimethylformamide and / or tetrahydrofuran, preferably a mixed solvent of N,N-dimethylformamide and tetrahydrofuran, further preferably a mixed solvent of N,N-dimethylformamide and tetrahydrofuran in a volume ratio of (5-2):(5-8), and most preferably a mixed solvent of N,N-dimethylformamide and tetrahydrofuran in a volume ratio of 2:8;
[0048] Preferably, the mass volume percentage (in g / ml) of the dielectric elastomer polymer to the solvent II is 15% to 25% (w / v), preferably 15%.
[0049] Preferably, in step 4), the electrospinning parameters are as follows:
[0050] The spinning distance is 14-16cm; the positive high voltage is 16-24kV, and the negative high voltage is 2kV; the spinning injection speed is 0.2mm / min-0.4mm / min; the spinning environment humidity is 50%-60%;
[0051] Further preferably, the parameters of the electrospinning are as follows:
[0052] The spinning distance is 16 cm; the positive high voltage is 16 kV, and the negative high voltage is 2 kV; the spinning injection speed is 0.25 mm / min; and the spinning environment humidity is 55%.
[0053] In a feasible embodiment, the total number of piezoelectric fiber composite structure layers obtained in step 5) is 2 layers, 4 layers, 6 layers, 8 layers or 10 layers.
[0054] Preferably, in step 6), the temperature of the hot pressing treatment is 25-40°C, the time of the hot pressing treatment is 1-10 min, and the pressure of the hot pressing treatment is 0.3-1 MPa.
[0055] Beneficial Effects
[0056] 1) It is difficult for a dielectric to achieve the coexistence of high polarization and high breakdown strength at the same time, and the improvement of a certain piezoelectric polymer often requires a relatively large cost. The present invention combines the advantages of the two dielectrics by constructing a multilayer structure in which piezoelectric fiber layers and dielectric elastomer layers are alternately stacked. At a limited cost, the technical effect of high breakdown strength and high polarization level is achieved, which provides a new strategy for the development of flexible sensors and piezoelectric nanogenerators with high sensitivity and high energy storage performance.
[0057] 2) In a preferred embodiment of the present invention, a conductive filler MXene is added to the piezoelectric fiber, and the electrostatic attraction between the abundant hydroxyl (-OH) groups on the surface of the MXene and the F or H atoms on the surface of the piezoelectric polymers P(VDF-HFP), PVDF, and PVDF-TrFE is utilized to form hydrogen bonds, and a dipole is formed under the action of an external electric field, thereby realizing the transformation of the α phase to the β phase of the piezoelectric polymers such as P(VDF-HFP), thereby improving their piezoelectric and dielectric properties.
[0058] 3) The piezoelectric fibers with added fillers such as MXene have enhanced dielectric constants without causing a significant increase in losses. The piezoelectric fibers with two different dielectrics in the multilayer structure achieve high breakdown strength and polarization levels. More importantly, the energy storage efficiency is improved. High energy storage efficiency and low loss are conducive to the long-term stable and efficient operation of piezoelectric nanogenerators. The multilayer piezoelectric nanofibers provide a new strategy for the development of piezoelectric nanogenerators with high sensitivity and high energy storage performance.
[0059] The possible mechanism of the present invention is that the rational design of the multilayer structure can adjust the electric field distribution to improve the breakdown field strength, suppress the dielectric loss, and thus obtain a higher energy density; in addition, the macroscopic interface between the layers of the multilayer structure can also suppress the enhancement of the breakdown path; the multilayer structure that combines polyurethane (as an insulating layer) with the PVDF-HFP piezoelectric functional layer in a layer-by-layer electrospinning manner can suppress charge injection, reduce dielectric loss, and combine the characteristics of the high dielectric constant of the PVDF-HFP functional layer and the high breakdown strength of the polyurethane layer, thereby comprehensively improving the energy storage performance of the composite fiber. In addition, polyurethane also has excellent mechanical properties, and its close combination with the PVDF-HFP layer improves the elongation of the composite fiber and reduces the elastic modulus of the composite fiber, so that the composite fiber has better flexibility, which is conducive to its practical application as a wearable flexible piezoelectric sensor.
[0060] In short, the multi-layered piezoelectric fiber composite material according to the present invention not only has excellent piezoelectric and dielectric properties, but also achieves the technical effect of high breakdown strength and high polarization level, thereby improving the sensitivity and energy storage density of the piezoelectric fiber material; in addition, the piezoelectric fiber composite material of the present invention also has excellent mechanical properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0061] One or more embodiments are exemplarily described by the pictures in the accompanying drawings, and these exemplary descriptions do not constitute limitations on the embodiments. The special word "exemplary" here means "used as an example, embodiment or illustrative". Any embodiment described as "exemplary" here is not necessarily interpreted as being superior or better than other embodiments.
[0062] Figure 1FT-IR spectra of comparative examples 1 to 4 of the present invention; wherein the abscissa is the wavelength and the ordinate is the transmittance.
[0063] Figure 2 The dielectric constant and dielectric loss images of comparative examples 1 to 4 of the present invention are shown in FIG. 1 , wherein: Figure 2 a shows that comparative examples 1 to 4 are 10 2 -10 6 The dielectric constant at frequency, Figure 2 b shows that comparative examples 1 to 4 are 2 -10 6 Dielectric loss under frequency; their horizontal axis is frequency, and the vertical axis is dielectric constant and dielectric loss respectively.
[0064] Figure 3 It is a comparison chart of the mechanical properties of Examples 1 to 8 of the present invention and Comparative Examples 1 to 4; wherein, Figure 3 a shows the mechanical properties of Comparative Example 1, Example 1, and Example 5, Figure 3 b shows the mechanical properties of Comparative Example 2, Example 2 and Example 6, Figure 3 c shows the mechanical properties of Comparative Example 3, Example 3 and Example 7, Figure 3 d shows the mechanical properties of Comparative Example 4, Example 4 and Example 8; their abscissas are strains and their ordinates are stresses.
[0065] Figure 4 is a ferroelectric curve diagram of Examples 1 to 8 of the present invention and Comparative Examples 1 to 4; wherein, Figure 4 a shows the ferroelectric curves of comparative examples 1 to 4, Figure 4 b shows the ferroelectric curves of Examples 1 to 4, Figure 4 c shows the ferroelectric curves of Examples 5 to 8; their abscissas are breakdown strength and their ordinates are electric displacement. DETAILED DESCRIPTION
[0066] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Unless otherwise expressly stated, throughout the specification and claims, the term "including" or its variations such as "comprising" or "including" will be understood to include the stated elements or components, without excluding other elements or other components.
[0067] In addition, in order to better illustrate the present invention, numerous specific details are provided in the specific embodiments below. It should be understood by those skilled in the art that the present invention can also be implemented without certain specific details. In some embodiments, raw materials, elements, methods, means, etc. well known to those skilled in the art are not described in detail, so as to highlight the main purpose of the present invention.
[0068] In the following examples, all the raw materials used are commercially available; among them, polyvinylidene fluoride-hexafluoropropylene was purchased from Sigma-Aldrich Company with an average molecular weight of 400,000; thermoplastic polyurethane (TPU), 1185A 10FHF antibacterial agent was purchased from BASF, Germany; titanium carbide aluminum (MAX 400 mesh) was purchased from Beijing Huawei Ruike Chemical Co., Ltd.; and MXene was prepared by the laboratory.
[0069] The preparation method of MXene is as follows:
[0070] 2 g LiF and 40 mL 9 M HCl were stirred in a polytetrafluoroethylene container for 30 min; then, 2 g Ti3AlC2 was slowly added at 35 °C and stirring was continued for 72 h; then, the reaction solution was centrifuged (3500 rpm, 10 min) and washed with deionized water, and then placed in a high-power ultrasonic machine (180 W, 40 min) and centrifuged (3500 rpm, 10 min) several times until the liquid pH reached 6-7, and an ice water bath was required during ultrasound; the precipitated product was centrifuged with deionized water, ultrasonically treated (180 W, 10 min), and centrifuged at 3500 rpm for 3 min; finally, the supernatant was collected; the supernatant was freeze-dried until the solvent was completely volatilized, the black powder was collected and ground to obtain MXene.
[0071] Example 1
[0072] In this embodiment, the piezoelectric fiber composite material of the present invention is prepared by the following steps:
[0073] (1) 2 g of P(VDF-HFP) particles were dissolved in a mixed solvent of 6 mL of N,N-dimethylformamide (DMF) and 4 mL of acetone (Ac), and magnetically stirred at 40 °C for 12 h to completely dissolve the particles, thereby obtaining a P(VDF-HFP) spinning precursor solution;
[0074] (2) The P(VDF-HFP) spinning precursor solution obtained in step (1) is used to prepare the first piezoelectric fiber layer by electrospinning technology, the spinning distance of the spinning machine is 16 cm, the spinning positive high voltage is 16 kV, the spinning negative high voltage is 2 kV, the injection speed is 0.25 mm / min, and the spinning environment humidity is 55%-60%;
[0075] (3) 1.5 g of TPU particles were dissolved in a mixed solvent of 2 mL of N,N-dimethylformamide (DMF) and 8 mL of tetrahydrofuran (THF), and magnetically stirred at 40 °C for 12 h to completely dissolve them, thereby obtaining a TPU spinning precursor solution;
[0076] (4) On the substrate of the first piezoelectric fiber layer prepared in step (2), the TPU spinning precursor solution obtained in step (3) is used to prepare a first polyurethane fiber layer by electrospinning technology, the spinning distance of the spinning machine is 16 cm, the spinning positive high voltage is 16 kV, the spinning negative high voltage is 2 kV, the injection speed is 0.25 mm / min, and the spinning environment humidity is 55%-60%;
[0077] (5) Through the above-mentioned layer-by-layer electrospinning, a piezoelectric nanofiber composite layer with a double-layer structure is obtained, and then placed on a hot press at 40°C and 0.3 MPa for 20 minutes to make the piezoelectric fiber layer and the polyurethane fiber layer fit tightly to obtain the piezoelectric fiber composite material of the present invention.
[0078] Example 2
[0079] In this embodiment, the piezoelectric fiber composite material of the present invention is prepared by the following steps:
[0080] (1) 0.02 g of MXene powder (MXene dosage is 1 wt% of P(VDF-HFP)) was added to a mixed solvent of 6 mL of N,N-dimethylformamide (DMF) and 4 mL of acetone (Ac), and ultrasonicated at 40 kHz and 100 W for 1 hour and then stirred for 1 hour to make it completely dispersed; then, 2 g of P(VDF-HFP) particles were dissolved in the above mixed solution and magnetically stirred at 40 °C for 12 hours to make it completely dissolved, thereby obtaining a P(VDF-HFP) / MXene spinning precursor solution;
[0081] (2) The P(VDF-HFP) / MXene spinning precursor solution obtained in step (1) is used to prepare the first piezoelectric fiber layer by electrospinning technology, the spinning distance of the spinning machine is 16 cm, the spinning positive high voltage is 16 kV, the spinning negative high voltage is 2 kV, the injection speed is 0.25 mm / min, and the spinning environment humidity is 55%-60%;
[0082] (3) 1.5 g of TPU particles were dissolved in a mixed solvent of 2 mL of N,N-dimethylformamide (DMF) and 8 mL of tetrahydrofuran (THF), and magnetically stirred at 40 °C for 12 h to completely dissolve the particles, thereby obtaining a TPU spinning precursor solution;
[0083] (4) On the substrate of the first piezoelectric fiber layer prepared in step (2), the TPU spinning precursor solution obtained in step (3) is used to prepare a first polyurethane fiber layer by electrospinning technology, the spinning distance of the spinning machine is 16 cm, the spinning positive high voltage is 16 kV, the spinning negative high voltage is 2 kV, the injection speed is 0.25 mm / min, and the spinning environment humidity is 55%-60%;
[0084] (5) Through the above-mentioned layer-by-layer electrospinning, a piezoelectric nanofiber composite layer with a double-layer structure is obtained, and then placed on a hot press at 40°C and 0.3 MPa for 20 minutes to make the piezoelectric fiber layer and the polyurethane fiber layer fit tightly to obtain the piezoelectric fiber composite material of the present invention.
[0085] Example 3
[0086] Same as Example 2, except that the amount of MXene powder added in step (1) is 0.04 g (the amount of MXene is 3 wt % of P(VDF-HFP)).
[0087] Example 4
[0088] Same as Example 2, except that the amount of MXene powder added in step (1) is 0.06 g (the amount of MXene is 3 wt % of P(VDF-HFP)).
[0089] Example 5
[0090] The same as Example 1, the only difference is that in step (5), the electrospun layers are formed into a four-layer structure, which is a P (VDF-HFP) fiber layer, a TPU fiber layer, a P (VDF-HFP) fiber layer, and a TPU fiber layer from bottom to top.
[0091] Example 6
[0092] The same as Example 2, the only difference is that in step (5), the electrospun layers are formed into a four-layer structure, which is P(VDF-HFP) / Mxene fiber layer, TPU fiber layer, P(VDF-HFP) / Mxene fiber layer, and TPU fiber layer from bottom to top.
[0093] Example 7
[0094] The same as Example 3, the only difference is that the electrospun layers are four-layered, which are P(VDF-HFP) / MXene fiber layer, TPU fiber layer, P(VDF-HFP) / MXene fiber layer, and TPU fiber layer from bottom to top.
[0095] Example 8
[0096] The same as Example 4, the only difference is that the electrospun layers are four-layered, which are P(VDF-HFP) / MXene fiber layer, TPU fiber layer, P(VDF-HFP) / MXene fiber layer, and TPU fiber layer from bottom to top.
[0097] Comparative Example 1
[0098] (1) 2 g of P(VDF-HFP) particles were dissolved in a mixed solvent of 6 mL of N,N-dimethylformamide (DMF) and 4 mL of acetone (Ac), and magnetically stirred at 40 °C for 12 h to completely dissolve the particles, thereby obtaining a P(VDF-HFP) spinning precursor solution;
[0099] (2) The P(VDF-HFP) spinning precursor solution obtained in step (1) is used to prepare piezoelectric nanofibers by electrospinning technology. The spinning distance of the spinning machine is 16 cm, the positive spinning high voltage is 16 kV, the negative spinning high voltage is 2 kV, the injection speed is 0.25 mm / min, and the spinning environment humidity is 55%-60%.
[0100] Comparative Example 2
[0101] (1) 0.02 g of MXene powder (MXene dosage is 1 wt% of P(VDF-HFP)) was added to a mixed solvent of 6 mL of N,N-dimethylformamide (DMF) and 4 mL of acetone (Ac), and ultrasonicated at 40 kHz and 100 W for 1 hour and then stirred for 1 hour to make it completely dispersed;
[0102] (2) Dissolve 2 g of P(VDF-HFP) particles in the above mixed solution and stir magnetically for 12 h at 40 °C to completely dissolve them to obtain a P(VDF-HFP) / MXene spinning precursor solution;
[0103] (3) The P(VDF-HFP) spinning precursor solution obtained in step (2) is used to prepare piezoelectric nanofibers through electrospinning technology, the spinning distance of the spinning machine is 16 cm, the spinning positive high voltage is 16 kV, the spinning negative high voltage is 2 kV, the injection speed is 0.25 mm / min, and the spinning environment humidity is 55%-60%.
[0104] Comparative Example 3
[0105] The same as comparative example 2, except that the amount of MXene powder added in step (1) is 0.04 g (the amount of MXene is 2 wt% of P(VDF-HFP)).
[0106] Comparative Example 4
[0107] The same as comparative example 2, except that the amount of MXene powder added in step (1) is 0.06 g (the amount of MXene is 3 wt% of P(VDF-HFP)).
[0108] Performance and effect test examples
[0109] 1. FT-IR determination of β-phase content of nanofibers
[0110] The specific detection methods are as follows:
[0111] The chemical structure of the nanofibers prepared in Comparative Examples 1-4 was determined using a Nicolet-38 Fourier transform infrared spectrometer (Thermoelectric Co., West Chester, PA, USA) to obtain FT-IR spectra, as shown in FIG. Figure 1 As shown; and, the vibration band area was analyzed and calculated by OMINC software to obtain its β phase content; the results are shown in the following Table 1.
[0112] Table 1. β-phase content of nanofibers prepared in Comparative Examples 1-4.
[0113] sample F(β) Comparative Example 1 89% Comparative Example 2 90% Comparative Example 3 93% Comparative Example 4 95.7%
[0114] 2. Dielectric constant and dielectric loss detection
[0115] The specific detection methods are as follows:
[0116] The test was performed using a BDS40 broadband dielectric impedance spectrometer (NOVOCONTROL, Germany). Specifically, the nanofiber samples prepared in Comparative Examples 1-4 were cut into circles with a diameter of φ = 20 mm, and then sandwiched between the upper and lower copper electrodes. 1 ~10 6 The dielectric constant and dielectric loss are measured in the Hz frequency range; the results are shown in Figure 2 and the following Table 2.
[0117] Table 2, Comparative Examples 1-4 Nanofiber Materials at 10 3 Dielectric constant and dielectric loss at Hz
[0118]
[0119]
[0120] 3. Mechanical properties testing
[0121] The specific detection methods are as follows:
[0122] High temperature tensile testing machine test, Suzhou Gaopin Testing Instrument Co., Ltd., test temperature is room temperature, test speed is 50mm / min. The elastic modulus of the composite material is determined by the stress-strain curve at 5% strain. The experimental data of the elastic modulus is the average of the results of at least three specimens under the same conditions.
[0123] The mechanical properties test results of the piezoelectric fiber composite materials obtained in the above examples 1-8 and the piezoelectric nanofibers obtained in the comparative examples 1-4 are shown in Figure 3 And the following Tables 3 to 6.
[0124] Table 3. Mechanical properties parameters of nanofiber materials of Comparative Example 1, Example 1 and Example 5
[0125] sample Elongation at break (%) Tensile strength(MPa) Elastic modulus (MPa) Comparative Example 1 176 6.8 5.84 Example 1 181 5.4 2.99 Example 5 177 2.7 2.91
[0126] Table 4. Mechanical properties parameters of nanofiber materials of Comparative Example 2, Example 2 and Example 6
[0127] sample Elongation at break (%) Tensile strength(MPa) Elastic modulus (MPa) Comparative Example 2 192 6.58 4.8 Example 2 187 5.3 3.5 Example 6 190 3.9 2.8
[0128] Table 5. Mechanical properties of nanofiber materials of Comparative Example 3, Example 3 and Example 7
[0129] sample Elongation at break (%) Tensile strength(MPa) Elastic modulus (MPa) Comparative Example 3 205 7.3 5.6 Example 3 206 6.5 4.7 Example 7 212 3.7 3.8
[0130] Table 6. Mechanical properties parameters of nanofiber materials of Comparative Example 4, Example 4 and Example 8
[0131]
[0132]
[0133] 4. Ferroelectric performance testing
[0134] The specific detection methods are as follows:
[0135] The ferroelectric energy storage properties of the composite fibers were studied using a TFAnalyzer 2000EF ferroelectric analyzer (aixACCT Co., Eschweiler, Germany). Specifically, the nanofiber samples were cut into circles with a diameter of 5-6 mm, and conductive copper tapes of the same shape and size were tightly adhered to the upper and lower surfaces of the samples to test the ferroelectric properties. The test frequency of the ferroelectric test was 10 Hz, and the test voltage range was 0.1-10 kV.
[0136] The ferroelectric properties of the piezoelectric fiber composite materials obtained in the above examples 1-8 and the piezoelectric nanofibers obtained in the comparative examples 1-4 are shown in FIG. Figure 4 and the following Tables 7-9.
[0137] Table 7. Maximum polarization value, breakdown strength and energy storage density of the nanofiber materials of Comparative Examples 1-4.
[0138]
[0139] Table 8. Maximum polarization values, breakdown strength and energy storage density of the nanofiber materials of Examples 1-4.
[0140]
[0141] Table 9. Maximum polarization values, breakdown strength and energy storage density of the nanofiber materials of Examples 5-8.
[0142]
[0143]
[0144] in conclusion
[0145] P(VDF-HFP) has three main crystal structures: α, β, and γ. Among them, the β phase shows the best piezoelectric response. The piezoelectricity of P(VDF-HFP) is mainly related to the content of the β phase. Generally speaking, the higher the β phase content, the stronger the piezoelectric output of P(VDF-HFP). The relative content of the β phase can be calculated by infrared spectroscopy analysis and Lambert-Beer's law.
[0146] The piezoelectric nanofibers prepared in Comparative Examples 1, 2, 3, and 4 were tested by infrared (the results are shown in FIG. Figure 1 As shown in the figure, the β-phase content of P(VDF-HFP) nanofibers with added MXene increases compared with pure P(VDF-HFP); and when the addition amount of MXene reaches 1%, 2%, and 3%, the β-phase content reaches 90%, 93%, and 95.6%, respectively. The higher the β-phase content, the better the piezoelectric performance of P(VDF-HFP).
[0147] By comparing and analyzing the dielectric images of the piezoelectric nanofibers prepared in Comparative Examples 1, 2, 3, and 4 (see Figure 2 ) shows that the addition of MXene can enhance the dielectric constant; when the addition amount of MXene reaches 0%, 1%, 2%, and 3%, at a frequency of 10 3 The dielectric constants under these conditions reached 2.2, 2.5, 2.6, and 2.9, respectively, and the dielectric losses were 0.03, 0.023, 0.06, and 0.025, respectively; that is, the dielectric constant was improved and the loss did not change significantly; thus, it can be seen that the addition of MXene is beneficial to improving the dielectric properties of piezoelectric fibers, enhancing the interfacial polarization and maintaining low losses.
[0148] Comparison of mechanical properties of the piezoelectric fiber composites prepared by Examples 1, 2, 3, 4, 5, 6, 7, 8 and the piezoelectric nanofibers prepared by Comparative Examples 1, 2, 3, 4 (see Figure 3) It can be obtained that the piezoelectric fiber of the multilayer structure has lower tensile strength and elastic modulus under the elongation rate; wherein, by comparing and analyzing Example 4, Example 8 and Comparative Example 4, it can be found that the tensile strength of the piezoelectric fiber gradually decreases, the single-layer structure is 9.5MPa, the double-layer structure is 6.7MPa, and the four-layer structure is 4.3MPa; the elastic modulus also gradually decreases, the single-layer structure is 5.84MPa, the double-layer structure is 5.45MPa, and the four-layer structure is 4MPa. It can be seen that the design of the multilayer structure makes the piezoelectric fiber more flexible, and the elongation is also slightly increased. Among them, by comparing and analyzing Examples 5, 6, 7, and 8, it can be found that the elongation at break of the piezoelectric fiber is slightly improved. When the addition amount of MXene reaches 0%, 1%, 2%, and 3%, the elongation at break of the piezoelectric fiber is 177%, 190%, 206%, and 230%, respectively.
[0149] Ferroelectric curves of the piezoelectric fiber composites prepared by Examples 1, 2, 3, 4, 5, 6, 7, and 8 and the piezoelectric nanofibers prepared by Comparative Examples 1, 2, 3, and 4 (see Figure 4 ) can be obtained, the design of the multi-layer structure can significantly improve the breakdown strength of the piezoelectric fiber; from the ferroelectric curves of comparative examples 1, 2, 3, and 4, the breakdown strength of the single-layer piezoelectric fiber is about 250 kV / cm, namely 220 kV / cm, 250 kV / cm, 266 kV / cm, and 270 kV / cm, respectively; from the ferroelectric curves of embodiments 1, 2, 3, and 4, the breakdown strength of the double-layer piezoelectric fiber is about 320 kV / cm, namely 300 kV / cm, 306 kV / cm, 320 kV / cm, and 360 kV / cm, respectively; from the ferroelectric curves of embodiments 5, 6, 7, and 8, the breakdown strength of the four-layer piezoelectric fiber is about 460 kV / cm, namely 420 kV / cm, 420 kV / cm, 460 kV / cm, and 540 kV / cm, respectively. In addition, the maximum polarization value is also improved, among which Example 8 has the largest polarization value (reaching 0.26 μC / cm 2 ), which is the maximum polarization value of comparative example 1 (0.11 μC / cm 2 ) is 2.4 times of that of Example 8; under the action of high polarization level and enhanced breakdown strength, the energy storage density of the multilayer piezoelectric fiber is greatly improved, among which the energy storage density of Example 8 reaches 71.7mJ / cm 3 , while the energy storage density of comparative examples 1 and 4 is only 12.03 mJ / cm 3 and 21.53mJ / cm 3 The piezoelectric fibers always maintain a high energy storage efficiency, wherein the energy storage efficiencies of Examples 5, 6, 7, and 8 all exceed 90%.
[0150] By comparing the piezoelectric sensitivities of Examples 1, 2, 3, 4, 5, 6, 7, 8 and Comparative Examples 1, 2, 3, 4, it can be found that the piezoelectric sensitivity of the multilayer structure design has high piezoelectric sensitivity in the low pressure detection range (<1 kPa); among them, when the addition amount of MXene reaches 3% and the four-layer structure design is used, the piezoelectric sensitivity reaches 0.38 kPa -1 .
[0151] It can be seen from the above embodiments, comparative examples and effect examples that the present invention improves the polar β phase content and dielectric properties of piezoelectric fibers such as P(VDF-HFP) by adding conductive fillers such as MXene, and reduces the tensile strength and elastic modulus of the piezoelectric fiber through multilayer structure design, improves the breakdown strength and polarization level, and makes the piezoelectric fiber have a higher energy storage density; more importantly, the multilayer structure piezoelectric fiber has high piezoelectric sensitivity in the low voltage detection range.
[0152] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A piezoelectric fiber composite material, characterized in that: The piezoelectric fiber composite material is a multi-layer composite structure, which is made by alternately stacking piezoelectric fiber layers and dielectric elastomer fiber layers and undergoing a heat-pressing treatment; The structure of the piezoelectric fiber composite material is as follows from bottom to top: (piezoelectric fiber layer-dielectric elastomer fiber layer) n; Wherein, n is an integer between 1 and 10; The piezoelectric fiber layer is made of piezoelectric polymer doped with conductive fillers through an electrostatic spinning process; Wherein, the piezoelectric polymer is selected from: P(VDF-HFP), PVDF, PVDF-TrFE, PAN; The conductive filler is MXene; In the piezoelectric fiber layer, the doping amount of the conductive filler accounts for 2wt%-3wt% of the piezoelectric polymer; The parameters of the electrospinning process of the piezoelectric fiber layer are as follows: The spinning distance is 14-16cm; the positive high voltage is 14-17kV, and the negative high voltage is 2kV; the spinning injection speed is 0.2mm / min-0.4mm / min; the spinning environment humidity is 50%-60%; The dielectric elastomer fiber layer is made of a dielectric elastomer polymer through an electrostatic spinning process; Wherein, the dielectric elastomer polymer is selected from: polyurethane or polyacrylate; The electrospinning process parameters of the dielectric elastomer fiber layer are as follows: The spinning distance is 14-16cm; the positive high voltage is 16-24kV, and the negative high voltage is 2kV; the spinning injection speed is 0.2mm / min-0.4mm / min; the spinning environment humidity is 50%-60%; The preparation method of the MXene is as follows: 2 g LiF and 40 mL 9 M HCl were stirred in a polytetrafluoroethylene container for 30 min; then, 2 g Ti3AlC2 was slowly added at 35°C and stirring was continued for 72 h; then, the reaction solution was centrifuged at 3500 rpm for 10 min and washed with deionized water, and then placed in a 180 W high-power ultrasonic machine for 40 min and centrifuged at 3500 rpm for 10 min several times until the liquid pH reached 7, and an ice water bath was required during ultrasound; the precipitated product was centrifuged with deionized water, ultrasonicated at 180 W for 10 min, and centrifuged at 3500 rpm for 3 min; finally, the supernatant was collected; the supernatant was freeze-dried until the solvent was completely evaporated, the black powder was collected and ground to obtain MXene.
2. The piezoelectric fiber composite material according to claim 1, characterized in that: The piezoelectric polymer is P(VDF-HFP).
3. The piezoelectric fiber composite material according to claim 1, characterized in that: The n is an integer between 1-5.
4. The piezoelectric fiber composite material according to any one of claims 1 to 3, characterized in that: The temperature of the hot pressing treatment is 25-40° C., the time of the hot pressing treatment is 1-10 min, and the pressure of the hot pressing treatment is 0.3-1 MPa.
5. The method for preparing a piezoelectric fiber composite material according to any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: 1) adding a conductive filler into solvent I, stirring by ultrasonic until uniform dispersion, then adding a piezoelectric polymer thereto, heating and stirring, to obtain a piezoelectric polymer solution doped with a conductive filler; 2) electrospinning the piezoelectric polymer solution obtained in step 1) to obtain a first piezoelectric fiber layer; 3) dissolving the dielectric elastomer polymer in solvent II, heating and stirring to obtain a dielectric elastomer polymer solution; 4) electrospinning the dielectric elastomer polymer solution obtained in step 3) on the first piezoelectric fiber layer obtained in step 2) to obtain a first dielectric elastomer fiber layer; 5) According to the method of steps 2) and 4), the piezoelectric fiber layer and the dielectric elastomer fiber layer are spun layer by layer from bottom to top in an alternating order to prepare a piezoelectric fiber composite structure layer; 6) The piezoelectric fiber composite structure layer obtained in step 5) is subjected to heat pressing treatment to tightly combine adjacent piezoelectric fiber layers and dielectric elastomer fiber layers to obtain the piezoelectric fiber composite material.
6. The preparation method according to claim 5, characterized in that: In step 1), the conductive filler is MXene; The piezoelectric polymer is selected from: P(VDF-HFP), PVDF, PVDF-TrFE or PAN; The solvent I is N,N-dimethylformamide and / or acetone; The amount of the conductive filler is 2wt%-3wt% of the amount of the piezoelectric polymer; The mass volume percentage of the piezoelectric polymer to the solvent I is 20 w / v% to 25 w / v%; The ultrasound frequency in step 1) is 40 kHz, the power is 60-100 W, and the ultrasound time is 0.5-4 h.
7. The preparation method according to claim 6, characterized in that: The piezoelectric polymer is P(VDF-HFP).
8. The preparation method according to claim 6, characterized in that: The solvent I is a mixed solvent of N,N-dimethylformamide and acetone.
9. The preparation method according to claim 8, characterized in that: The solvent I is a mixed solvent of N,N-dimethylformamide and acetone in a volume ratio of (3-2): (2-3).
10. The preparation method according to claim 9, characterized in that: The solvent I is a mixed solvent of N,N-dimethylformamide and acetone in a volume ratio of 3:
2.
11. The preparation method according to any one of claims 6 to 10, characterized in that: The mass volume percentage of the piezoelectric polymer in the solvent I is 20 w / v%.
12. The preparation method according to any one of claims 5 to 10, characterized in that: In step 2), the electrospinning parameters are as follows: The spinning distance is 14-16cm; the positive high voltage is 14-17kV, and the negative high voltage is 2kV; the spinning injection speed is 0.2mm / min-0.4mm / min; and the spinning environment humidity is 50%-60%.
13. The preparation method according to claim 12, characterized in that: In step 2), the electrospinning parameters are as follows: The spinning distance is 16 cm; the positive high voltage is 16 kV, and the negative high voltage is 2 kV; the spinning injection speed is 0.25 mm / min; and the spinning environment humidity is 55%-60%.
14. The preparation method according to claim 5, characterized in that: In step 3), the dielectric elastomer polymer is selected from: polyurethane or polyacrylate; The solvent II is N,N-dimethylformamide and / or tetrahydrofuran, The mass volume percentage of the dielectric elastomer polymer to the solvent II is 15 w / v% to 25 w / v%.
15. The preparation method according to claim 14, characterized in that: The solvent II is a mixed solvent of N,N-dimethylformamide and tetrahydrofuran.
16. The preparation method according to claim 15, characterized in that: The solvent II is a mixed solvent of N,N-dimethylformamide and tetrahydrofuran in a volume ratio of (5-2):(5-8).
17. The preparation method according to claim 16, characterized in that: The solvent II is a mixed solvent of N,N-dimethylformamide and tetrahydrofuran in a volume ratio of 2:
8.
18. The preparation method according to any one of claims 14 to 17, characterized in that: The mass volume percentage of the dielectric elastomer polymer to the solvent II is 15 w / v %.
19. The preparation method according to any one of claims 5 to 10, characterized in that: In step 4), the electrospinning parameters are as follows: The spinning distance is 14-16cm; the positive high voltage is 16-24kV, and the negative high voltage is 2kV; the spinning injection speed is 0.2mm / min-0.4mm / min; and the spinning environment humidity is 50%-60%.
20. The preparation method according to claim 19, characterized in that: In step 4), the electrospinning parameters are as follows: The spinning distance is 16 cm; the positive high voltage is 16 kV, and the negative high voltage is 2 kV; the spinning injection speed is 0.25 mm / min; and the spinning environment humidity is 55%.
21. The preparation method according to any one of claims 5 to 10, characterized in that: Step 5) The total number of layers of the obtained piezoelectric fiber composite structure layer is 2 layers, 4 layers, 6 layers, 8 layers or 10 layers.
22. The preparation method according to any one of claims 5 to 10, characterized in that: In step 6), the temperature of the hot pressing treatment is 25-40° C., the time of the hot pressing treatment is 1-10 min, and the pressure of the hot pressing treatment is 0.3-1 MPa.
Citation Information
Patent Citations
Multilayer polymer nanocomposite and preparation method thereof
CN110341205A
Flexible sensor, preparation method and application thereof, and wearable device
CN113280954A